Diseño de un sistema de gestión de calidad bajo la NTC ISO 9001:2015 para la empresa alca ingeniería y desarrollo S.A.S (2021)
Nowadays it's important to complete the requirements, needs and demands of each of the customers, obtaining a high level of competitiveness, product of a globalized market, most companies that want to stay active for a long time, see the need to find tools that allow them distinction from competition. That is why ALCA INGENIERÍA Y DESARROLLO S.A.S.